PENGARUH BAHASA PERTAMA TERHADAP PROSES BELAJAR BAHASA KEDUA - Deny Pratama (Jurnal Komposisi, 2021)
The purpose of this study is to understand how the first language affects learning a second language. The study is a study in psychoolinguistics the subject of the study is six-year-olds, with madura (the first language) as madura and the second language is Indonesian. The study USES qualitative descriptive methods with a string of string phenomena. Studies have shown the impact of the first language, with the everyday speech of children. The data shows the blending of the first language with the second language. The causes of the influence of the first language are due to the lack of training in English in a daily life, and the use of Indonesian only in school, which is affected by the time both child and mistake (mistake), mistake.